2012
DOI: 10.1080/10228195.2012.654501
|View full text |Cite
|
Sign up to set email alerts
|

English in the mix: Evolving roles of English in the language practices of Twi speakers in Ghana

Abstract: This article is concerned with language alternation between Twi and English in informal conversation . Twi is the most widely spoken indigenous language of Ghana, also used in the broadcast media, especially radio; English, the former colonial language, is the official language, and the main language of the education system and print media. However, English is now gradually encroaching on domestic and informal domains, and younger urban speakers are increasingly shifting towards English as a first language . P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As briefly explained in Section 2, these varieties were chosen in order to carry out a first investigation of the widely diverging frequencies in the corpus in texts from communities in which English has, generally speaking, different currency and uses. The two African and Asian locations were selected to represent this ecological diversity, with Ghana and Singapore generally displaying a wider range of established uses of English in different domains, as well as a more established tradition of favourable attitudes to English as a prestigious language (Arthur‐Shoba & Quarcoo, ; Cavallaro, Ng, & Seilhamer, ). Jamaica was added to include a representative of Caribbean Englishes, as these are also in competition with creoles, especially in colloquial registers.…”
Section: Forms and Meanings Of I'm Afraid In Selected Varietiesmentioning
confidence: 99%
“…As briefly explained in Section 2, these varieties were chosen in order to carry out a first investigation of the widely diverging frequencies in the corpus in texts from communities in which English has, generally speaking, different currency and uses. The two African and Asian locations were selected to represent this ecological diversity, with Ghana and Singapore generally displaying a wider range of established uses of English in different domains, as well as a more established tradition of favourable attitudes to English as a prestigious language (Arthur‐Shoba & Quarcoo, ; Cavallaro, Ng, & Seilhamer, ). Jamaica was added to include a representative of Caribbean Englishes, as these are also in competition with creoles, especially in colloquial registers.…”
Section: Forms and Meanings Of I'm Afraid In Selected Varietiesmentioning
confidence: 99%
“…39, 41), and a feeling that the language being shifted from is inferior to the one being shifted to (Fasold, ; Omoniyi, , p. 181). The literature on language practices in educated families in Anglophone (and possibly francophone and lusophone) Africa's urban centers shows that children in those families have shifted or are gradually shifting to English at the expense of their indigenous languages (see, for instance, Bowerman, ; V. de Klerk, ; Kamwangamalu, , ; McDuling & Barnes, ; Prabhakaran, for South Africa; Smeija, 1998, and Nyati‐Ramahobo, for Botswana; Adegbija, , Igboanusi & Peter, , and Ugwuanyi, for Nigeria; Kayambazhintu, for Malawi; and Arthur‐Shoba & Quarco, for Ghana). The central finding in all these studies is that the shift to English has already happened for some (for example, South African Indians); is on the way for others (such as the younger generations in educated urban families); and is, as V. de Klerk (, p. 105) puts it in the context of South Africa, almost irrevocable.…”
Section: English As An African Languagementioning
confidence: 99%
“…The study finds English terms that are pronounced differently by school pupils in the Bono and Ahafo Regions of Ghana owing to ignorance of the target language, hearing difficulties, or most crucially first language influence (Riaz, 2021). According to some (e.g., (Arthur-Shoba & Quarcoo, 2012)), Ghanaian English (GhE) is a "new" variation of English. (Adjaye, 2005;Huber et al, 2008;Koranteng, 2006) all identified distinctive structural and phonological traits as well as lexical elements Dako, (2001) referred to as "Ghanaianisms" that reflect the local cultural and linguistic milieu.…”
Section: Introductionmentioning
confidence: 99%